FORMULATION OF WHEY-SWEET ORANGE BASED READY-TO-SERVE FRUIT BEVERAGE - P. ASHOK KUMAR; P. BANGARAIAH (International Journal of Pharma and Bio Sciences, 2014)
Whey is the largest by-product of huge dairy industry and is one of the most troublesome byproduct produced which in Biological Oxygen Demand (BOD) value of waste water making the disposal costly and problematic. Whey based beverages with different concentrations of sweet orange juice and standard ingredients of RTS beverage were prepared. These beverages were analyzed for physic chemical parameters like pH, acidity, TSS, ascorbic acid, total sugars, reducing sugars, lycopene, microbial quality (bacteria, yeast, and mold), shelf life and acceptability. The beverages were stored till spoilage and analysis was carried out at 15 days interval. The results indicated that on storage, acidity and reducing sugars increased significantly, whereas pH, total sugars, ascorbic acid and lycopene decreased significantly in all the treatments. TSS did not change appreciably during storage and no microbial growth was observed up to 30 days. Scores for all sensory parameters decreased with the increase in storage period. Significant decrease in scores was observed after 45 days to 60 days of storage.